1994
DOI: 10.1084/jem.179.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Distinct types of lung disease caused by functional subsets of antiviral T cells.

Abstract: SummaryT cells appear to play a central role in viral bronchiolitis, but the effects of different functional and phenotypic subgroups ofT cells have not been defined. To test the activities ofT cells recognizing individual proteins of respiratory syncytial (RS) virus, virus-specific T cell lines were produced from mice primed by scarification with recombinant vaccinia viruses expressing the major surface glycoprotein (G), fusion protein (F) or second matrix (22K) protein of KS virus. As previously reported, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
211
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(226 citation statements)
references
References 39 publications
12
211
1
2
Order By: Relevance
“…Not only does this factor not alter protection of mice against viral replication, it might also contribute to the reduced numbers of infiltrating eosinophils observed after RSV challenge. Indeed, RSVspecific CD8 + T cells have been implicated in the pathology linked with both neutrophil and eosinophil infiltrates upon infection [16,17]. These elements are further evidence that, while CTL might be the main factor contributing to the resolution of primary RSV infection, they are dispensable and possibly deleterious in vaccine-induced protection against re-infection and lung pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only does this factor not alter protection of mice against viral replication, it might also contribute to the reduced numbers of infiltrating eosinophils observed after RSV challenge. Indeed, RSVspecific CD8 + T cells have been implicated in the pathology linked with both neutrophil and eosinophil infiltrates upon infection [16,17]. These elements are further evidence that, while CTL might be the main factor contributing to the resolution of primary RSV infection, they are dispensable and possibly deleterious in vaccine-induced protection against re-infection and lung pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the ability of iRSV to prime for a Th2 response, thus leading to an inappropriate response, highlighted by substantial eosinophilia in the lung after RSV challenge at least in animal models. Previous animal studies have delivered the iRSV mainly by the intramuscular route, although other studies have delivered vaccinia virus constructs carrying the RSV G protein by scarification at the base of the tail [14][15][16]. These methods of immunisation prime for a Th2 response in the lung after RSV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, mice previously immunized with a recombinant vaccinia virus expressing the gene encoding the RSV-G glycoprotein will, upon challenge intranasal RSV infection, develop a CD4 + T cell Th2 type response in the lungs characterized by elevated levels of eosinophils in the BAL fluid and lung parenchyma (Openshaw et al 1992), (Alwan et al 1994), (Varga et al 2000).…”
Section: Identification Of Cd11c Low/− Siglec-f + Eosinophils In the mentioning
confidence: 99%
“…chicken egg albumin administration), and in murine models of respiratory virus infection where type II CD4 + T cell responses play a prominent role [e.g. challenge Respiratory Syncytial Virus (RSV) infection of immune mice (Openshaw et al 1992), (Srikiatkhachorn and Braciale 1997), (Johnson et al 1998), (Alwan et al 1994), (Varga et al 2000), (Varga et al 2001)]. …”
Section: Introductionmentioning
confidence: 99%
“…Asthma is characterised by a bias towards Th2 responses, associated frequently with airway eosinophilia. In a mouse model of RSV disease, sensitisation with recombinant vaccinia expressing the viral glycoprotein G primes for a strong Th2 biased immune response that causes lung eosinophilia during intranasal infection with RSV [10]. G can be mutated at the second initiation codon to prevent secretion of the glycoprotein, and sensitisation with recombinant RSV expressing only the membrane bound (non-secreted) form of the G protein induces significantly less of an eosinophilic response during RSV challenge [11].…”
Section: Introductionmentioning
confidence: 99%